Three new replacement names for beetle genera in Cerylonidae, Zopheridae and Cerambycidae (Insecta: Coleoptera) - Ślipiński, Adam (Zootaxa, 2016)
This note resolves homonymy among three genera of beetles described by myself (Ślipiński 1988, 1990), John F. Lawrence (Ślipiński & Lawrence 1997), and Hermes E. Escalona (Ślipiński & Escalona 2016). I propose new replacement names in accordance with the International Code of Zoological Nomenclature (ICZN 1999). Two anonymous reviewers are thanked for making valuable suggestions on an earlier version of this manuscript.